Studying cardiac contractility change trend to evaluate cardiac reserve. - Shouzhong Xiao (IEEE Engineering in medicine and biology magazine)
There is a very close relationship between the amplitude of the first heart sound and the cardiac contractility. We previously presented the concept of cardiac contractility variability (CCV) and an analysis method. On the basis of the findings from the authors' observation and other previous studies, a conclusion can be made that the variability of the first heart sound amplitude is a reflection of CCV. We found that an increase of the amplitude of the first heart sound can be seen on the phonocardiogram obtained even after a small workload exercise. We defined the increase of the amplitude of the first heart sound after accomplishing different exercise workloads, with respect to the amplitude of the first heart sound recorded at rest as cardiac contractility change trend (CCCT). CCCT implies information about cardiac contractility and cardiac reserve. To explore the significance of CCCT for evaluating cardiac contractility reserve of a patient or an athlete, we carried out a study on cardiac contractility change trend, the methods and the results of which are presented.